2018
DOI: 10.5217/ir.2018.16.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Histologic discrepancy between endoscopic forceps biopsy and endoscopic mucosal resection specimens of colorectal polyp in actual clinical practice

Abstract: Background/AimsWe aimed to assess the rate of histologic discrepancy (HD) between endoscopic forceps biopsy (EFB) and totally resected specimens in colorectal polyp and analyze the risk factors of discordant group, especially under-diagnosis (UD) cases before complete removal of colorectal polyp.MethodsFrom 2010 to 2015, a total of 290 polyps in 210 patients which had baseline pathology report before endoscopic resection (ER) were analyzed. UD cases were defined as those in which the diagnosis changed to a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…We are convinced that the larger size of target lesions could potentially increase rates of histopathologic discrepancies [32]. Our result has veri ed ≥ 1.0 cm could be a signi cant cut-off value to predict upgrade histopathology in accordance with the previous studies [10]. 1.0 cm is also considered as a cut-off value of advanced adenomas, which is another reason we used [33].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We are convinced that the larger size of target lesions could potentially increase rates of histopathologic discrepancies [32]. Our result has veri ed ≥ 1.0 cm could be a signi cant cut-off value to predict upgrade histopathology in accordance with the previous studies [10]. 1.0 cm is also considered as a cut-off value of advanced adenomas, which is another reason we used [33].…”
Section: Discussionsupporting
confidence: 76%
“…Some studies also reported histology discrepancies of colorectal polyps but failed to gure out signi cantly useful predictors [23][24][25]. Recently, a retrospective study analyzing 290 polyps reported histologic discrepancies between pretreatment EFB and EMR specimens of colorectal polyps [10]. But their inclusion criteria are not relatively strict, and their sample size is relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the superficial forceps biopsy may not contain cancerous tissues, complete resection of the lesion is necessary for determining the histology accurately. 32 ER alone may be adequate for treating low-risk lesions. Although additional surgery may improve the survival outcomes for patients with high-risk lesions, the adverse events of surgery are not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…For the intraepithelial neoplasia in the digestive tract, it has been reported that there are some histopathological discrepancies between endoscopic forceps biopsy (EFB) and pathological outcomes of ER specimens, such as superficial esophageal squamous neoplasm, gastric epithelial neoplasia, and colorectal polyps [ 8 10 ], whereas few research has been conducted to analyze the factors predicting histopathologically upgrade discrepancies between EFBs of colorectal low-grade intraepithelial neoplasia (LGIN) and ER specimens demonstrating high-grade intraepithelial neoplasia (HGIN) or adenocarcinoma. Therefore, the aim of the present study was to explore these discrepancies and intend to elucidate the potential risk factors and traits contributing to this type of upgrade histopathological diagnosis for the colorectal adenomas with LGIN forceps biopsy, which could suggest us to make a further accurate diagnosis and guide the optimal clinical management for these lesions.…”
Section: Introductionmentioning
confidence: 99%